Respuesta :

Answer:

[tex]2\,log_5(x)-2\,log_5(4)[/tex] which is the third listed option

Step-by-step explanation:

We use the properties of logarithms, starting with the property for exponents ([tex]log_b(a^n)=n\,*\,log_b(a)[/tex]), so we get:

[tex]log_5(\frac{x}{4} )^2=2\,*\,log_5(\frac{x}{4} )[/tex]

and now we use the property of log of a quotient ([tex]log_b(\frac{x}{y} )=log_b(x)-log_b(y)[/tex]), which continuing with our case gives:

[tex]2\,*\,log_5(\frac{x}{4} )= 2\,*[log_5(x)-log_5(4)]=2\,log_5(x)-2\,log_5(4)[/tex]

This coincides with the third option listed among the possible answers

Answer:

The answer is c

Step-by-step explanation: